Language Shift and Maintenance: A Case Study of the Telugu Community in Bagan Datoh, Perak (Malaysia) - Polamarachetty, Kathreine Deva Babu; Riget, Patricia Nora (Journal of Modern Languages, 2023)
Telugu is an official language, commonly spoken in Andhra Pradesh and Telangana, India. Despite being one of the largest languages in the world, it is a minority language in Malaysia. Majority of the Telugus who migrated, settled in the plantation estates i.e Bagan Datoh, Perak (known as a Telugu heritage site). This study employs domain analysis to find out language choice in home, social, entertainment, religious and official domains among the younger and older generation as well as their language attitude. This study uses mixed methods. Questionnaire surveys were accompanied by interviews and focus groups discussions. Language shift is observed in literacy but being revitalized among the youngest generation. In spoken language, Telugu is well maintained especially in the home domain, coexisting with other languages in a diglossic relationship. Positive attitude towards mother tongue and revitalization endeavors demonstrate a favorable influence on the maintenance of the Telugu language in Bagan Datoh.